MicroRNA‐microbiota interactions: Emerging strategies for modulating intestinal homeostasis and enhancing host health - Tianle He; Jiaying Ma; Shuai Liu; Boyan Ma; Jingtao You; Jingjun Wang; Mengmeng Li; Wei Wang; Ya Jing Wang; Shengli Li; Zhijun Cao (iMetaOmics)
Abstract Long‐term artificial selection and environmental shifts have driven adaptive changes in both the host genome and the intestinal microbiota. The complex symbiotic relationship between these two has become essential for maintaining intestinal homeostasis and overall health. Concurrently, advancements in sequencing technology and the functional annotation of noncoding RNAs, particularly microRNAs (miRNAs), have facilitated the exploration of mechanisms regulating intestinal homeostasis. Herein, we systematically update the role of miRNA–microbiota interactions in regulating the intestinal barrier, intestinal immunity, changes in intestinal microbiota dynamics, and maintenance of intestinal homeostasis, and we further critically discuss the role of miRNA–microbiota interactions in the maintenance of host intestinal health, metabolic regularity, brain function, and neurodegenerative disease‐related disorders. Finally, we highlight the prospects and therapeutic strategies regarding miRNA–microbiota interactions in humans and animals in the context of intestinal microbiota and gene function studies. This study provides a comprehensive overview of miRNA–microbiota interactions and their influence on intestinal homeostasis and host health and offers novel therapeutic strategies for future personalized prevention and treatment of intestinal diseases.